Challenges in classifying Humanities and Social science materials of the Library University of Jaffna - Arulanantham, S.; Navaneethakrishnan, S. (LIS Research Symposium of the Library and Information Science Alumni Association, 2012)
The phenomenal aspects of universe of subjects and their increasing complexity has created tremendous challenges for researchers as well as the library staff dealing with organization of materials. Dewey decimal classification of Melvil Dewey shortly named as DDC is very popular among libraries for its wide usage worldwide. Commonly University libraries in Sri Lanka adopt DDC for organizing their materials. University libraries in which faceted scheme is more suitable than enumerative one for locating interdisciplinary subject in its proper place, face much problem in organizing materials using this scheme. Having been situated in a war torn area, the Library of the University of Jaffna is isolated with limited opportunities for national and international links and collaborations with higher educational institutions due to political, economic and social crisis and unrest in the past 25 years. Library has a major collection of materials for the readers of the Faculty of Arts the largest Faculty of the University of Jaffna includes 17 academic departments and provides study programmes in 24 disciplines on social sciences, humanities and aesthetic studies The objective of this research study is to identify the specific challenges faced in organizing Humanities and Social science materials in the library of the University of Jaffna using 22nd edition of Dewey decimal classification. Based on the descriptive analysis of the problems encountered in the last three years during the organization of humanities and social science materials at the library of University of Jaffna, this research paper provide a basic understanding to a classifier who is interested in depth classification in organizing complicated materials and formulate guiding principles for classifiers when dealing with interdisciplinary subjects. Identifying the subject of a document, Finding the class number of new subjects and incorporating them in their proper location, inconsistency in number building and the lengthy notations are identified as the major challenges in this study in organizing Humanities and Social science materials using 22nd edition of DDC. Applying Facet analytical approach for the document dealing with more than one subjects or discipline introduced in the colon scheme DDC may be of useful to the classifier to solve the problems in classifying complicated materials without violating the basic structure of DDC. It was also suggested to maintain a subject authority file which would indeed help to identify the relevant subject.
Keywords: Organization of Knowledge; Dewey decimal classification-practical aspects